2022
DOI: 10.1109/tbme.2021.3118229
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Power of Electroencephalogram Arousal Is Modulated by Respiratory Event Type and Severity in Obstructive Sleep Apnea

Abstract: We aimed to investigate the differences in electroencephalogram (EEG) gamma power (30-40 Hz) of respiratory arousals between varying types and severities of respiratory events, and in different sleep stages. Methods: Power spectral densities of EEG signals from diagnostic Type I polysomnograms of 869 patients with clinically suspected obstructive sleep apnea were investigated. Arousals were compared between sleep stages, as well as between the type (obstructive apnea and hypopnea), and duration (10-20 s, 20-30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…Azarbarzin et al [18] showed that the cardiovascular response also contains information on the arousal intensity. As obstruction type and the presence of desaturation, found to intensify the arousal response in the present study, have also been shown to strengthen the EEG changes in arousal [12] , [13] , the present study indirectly supports the findings of Azarbarzin et al [18] with a much larger subject population. The delays between the EEG arousal and the cardiovascular responses should also be taken into account when detecting arousals based on PPG if the timing of the arousals is considered important.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Azarbarzin et al [18] showed that the cardiovascular response also contains information on the arousal intensity. As obstruction type and the presence of desaturation, found to intensify the arousal response in the present study, have also been shown to strengthen the EEG changes in arousal [12] , [13] , the present study indirectly supports the findings of Azarbarzin et al [18] with a much larger subject population. The delays between the EEG arousal and the cardiovascular responses should also be taken into account when detecting arousals based on PPG if the timing of the arousals is considered important.…”
Section: Discussionsupporting
confidence: 90%
“…The American Academy of Sleep Medicine (AASM) defines an arousal as a sudden shift in the electroencephalogram (EEG) frequency [11] . The magnitude of the EEG activity change during an arousal is affected by the arousal-causing respiratory event severity (aspects such as obstruction type, i.e., apneas vs. hypopneas, and presence of blood oxygen desaturation) [12] , [13] .…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with the literature, where the interscorer agreement in EEG segment classification into arousals or stable sleep has been lower in R&K (Rechtschaffen & Kales, 1968) stages 1+2 than 3+4 (Drinnan et al, 1998). As EEG high‐frequency content related to arousals is known to increase more when the arousals occur in deep sleep compared to light sleep (Pitkänen et al, 2022), the EEG frequency shift indicating an arousal may be more easily distinguishable in deeper sleep.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the performance of the OSA screening improved when the model was trained by adding the number of arousals in addition to NREM/REM EEG features ( Supplementary Figure S3 ). Although the current study did not cover the contents related to the arousal index in-depth, given that the recent findings demonstrated that gamma power in EEG arousal differs according to the severity of the respiratory event and sleep stages ( Pitkänen et al, 2021 ), future studies may need to closely examine such characteristics and incorporate them into building the models as needed.…”
Section: Discussionmentioning
confidence: 99%